PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 BATANG KAPAS KABUPATEN PESISIR SELATAN - Yulianda, Ninil; Aima, Zulfitri; Haryono, Yulia (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was conducted due to the studentsâ low understanding on mathematics concepts. Therefore, Everyone is a Teacher Here (ETH) active learning strategy was applied. This research was aimed at revealing whether the conceptual understanding of the students taught by using ETH active learning strategy was better than that of students taught by using conventional learning in class VIII of SMPN 4 Batang Kapas. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII of SMPN Batang Kapas. The instrument of the research was a test whore reliability was 0,91. Based on the result of data analysis it was found that the sample classes were normally distributed and homogenous. As the value of tcalculated > ttable, the hypothesis was accepted indicating that the conceptual understanding of the students taught by using ETH active learning strategy was better than that of students taught by using conventional learning in class VIII of SMPN 4 Batang Kapas. Â